Recurrent schizophrenia-like psychosis as first manifestation of epilepsy: a diagnostic challenge in neuropsychiatry - Verhoeven, Willem MA (Dove Medical Press, 2010)
Since the 1950s, several studies have been carried out to investigate the occurrence of schizophrenia-like psychoses in epilepsy. The psychopathological profile comprises symptoms from the affective, schizophrenic, and cognitive domains and the prevalence varies between 2% to 20%. Classification of such conditions is performed according to their temporal relationship with the seizure itself. Although it is well known that epilepsy may be associated with psychotic disorders, it is less widely recognized that relapsing psychotic phenomena may be the first and only symptom of epilepsy. In this research, two patients are described who were initially referred for recurrent episodes of bipolar affective disorder and schizophrenic psychosis, respectively. In both patients, a diagnosis of relapsing postictal psychotic states due to previously undiagnosed epilepsy was made and consequently, treatment with antiepileptics was started. During follow up over several months, they remained free of both epileptic and psychotic symptoms. Given the kaleidoscopic nature of the postictal psychosis and full recovery from this, such psychoses best meet the criteria for a cycloid psychosis. These observations illustrate diagnostic and therapeutic pitfalls due to the conceptual disintegration emerging from the inadequate separation between psychiatry and neurology. Therefore, the importance of a neuropsychiatric viewpoint should be promoted.